THE MEANING ON MAIMUN PALACE ORNAMENTS: SEMIOTIC STUDY - Maura Annisa; Zuindra Zuindra; M.Kiki Wardana (Lembaga Pengembangan Kinerja Dosen, 2022)
The purpose of this study is how the writer found shape and meaning in the ornament in Maimun palace. The writer applied the theory of Semiotics proposed by Peirce (1978). The method is a qualitative research method, which is directly analyzes the facts found in the field. The writer obtained the data by conducting observations and interviews directly to the field, as well as getting information from several books and websites. The result showed that it was found some types of ornaments at the Maimun Palace. Then the writer compiled and described them based on the shape, namely ornament in the form of plant motifs, ornaments in the form of animal motifs, ornaments in the form of natural motifs, and ornaments in the form of calligraphy motifs. Then the writer explained the ornament based on its meaning contained in the Maimun Palace based on semiotic approach. The average function of the ornaments in the Maimun Palace is as decoration on the walls and the Sultan’s Throne.